A "Nephrological" Approach to Physical Activity - Filippo Aucella; Antonio Gesuete; Yuri Battaglia (Karger Publishers, 2014)
Despite consensus among nephrologists that exercise is important and probably beneficial for their patients, assessment of physical function or encouragement of physical activity is not a part of the routine management of patients with CKD. In order to plan an useful strategy for exercise training we need to clearly define some questions. First of all, nephrologists need to be aware of physical exercise benefits; lack of motivation and increased perceived risk by health care professionals have been identified as contributing factors to physical inactivity. Moreover, the main elements necessary for sustaining exercise programs in this population have to take in account, such as the requirement of exercise professionals, equipment and space, individual prescription, adequate commitment from dialysis and medical staff. When PA may not be implemented, a comprehensive, individualized occupational therapy program may improve functional independence and activity of daily living. Finally, physical function has to be careful monitored and assesses by medical staff.